Penerapan Algoritma Elias Omega Code Pada Aplikasi Kompresi File Citra - Rosmaida Rosmaida; Rivalri Kristianto Hondro (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Image file sizes are sometimes relatively large where the better the resulting image quality, the larger the pixel size needed to record the image. With a very large image file size, when carrying out the transfer process it fails because the storage space exceeds the limit. The solution to this problem is how the image file can be compressed in order to speed up the transfer and storage of image files. Compression of image files is done by reducing the size of the image file by reducing the bits in the image file, but not eliminating the information data in it. By compressing, large data will be reduced in size so as to save storage space. In this study, the algorithm used is the Elias Omega Code, using this method, the compression results of the values have different results for each value, and the compression results will be beneficial in sending, and moving image files will be easier.